SBRT in pancreatic cancer: What is the therapeutic window?. Issue 1 (January 2015) - Brunner, Thomas B.; Nestle, Ursula; Grosu, Anca-Ligia; Partridge, Mike
Abstract: Purpose/objective: To analyse outcome and toxicity of stereotactic body radiotherapy (SBRT) in pancreatic cancer (PDAC). Material/methods: We systematically reviewed full reports on outcome and toxicity transforming prescription doses to equivalent doses of 2 Gy (EQD2) and biological equivalent doses (BED). Pearson product-moment correlation coefficient, regression analysis and Lyman–Kutcher–Burman modelling were used. Results: Sixteen trials (572 patients) were identified. Local control correlated with dose. Additionally 4 upper gastrointestinal-SBRT trials (149 patients) were included for toxicity analysis. Acute toxicity was mild but late toxicity ⩾G2 was substantial and predominantly gastrointestinal. Late toxicity ⩾G2 and ⩾G3 correlated highly with EQD2/BED after linear ( R 2  = 0.85 and 0.77, respectively) and Lyman–Kutcher–Burman modelling. Linear regression lines indicated ⩾G2 and ⩾G3 toxicity frequencies of 5% at 65 Gy and 80 Gy EQD2-α/β = 3, respectively. A comparison of toxicity with dose constraints for duodenum revealed partly inadequate dose constraints. Conclusion: Results from multiple fraction regimens could be successfully interpreted to estimate toxicity according to EQD2/BED prescription doses, and dose constraints for the duodenum were derived, whereas local control appeared to be less dose-dependent. This analysis may be useful to plan clinical trials for SBRT and hypofractionated radiotherapy in pancreatic cancer.